2009
DOI: 10.1097/aco.0b013e32833037d2
|View full text |Cite
|
Sign up to set email alerts
|

Acute pain management in patients with fibromyalgia and other diffuse chronic pain syndromes

Abstract: The perioperative pain management of patients with fibromyalgia is challenging and should include symptom-based approaches to target enhanced central sensitization and decreased inhibition in these patients as well as their psychological syndromes aiming to decrease acute and prolonged pain after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 70 publications
0
12
0
1
Order By: Relevance
“…[ 4 ] Neuronal hypersensitivity and nociception after surgical incision are mainly maintained by afferent barrage of sensitized nociceptors across the postoperative period. [ 22 ] Thus, it is suggested that both analgesic and antihyperalgesic interventions are necessary in a postsurgical setup. The peripheral nociceptive stimuli also cause a neuroendocrine stress response, affecting various systems of our body leading to increased perioperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] Neuronal hypersensitivity and nociception after surgical incision are mainly maintained by afferent barrage of sensitized nociceptors across the postoperative period. [ 22 ] Thus, it is suggested that both analgesic and antihyperalgesic interventions are necessary in a postsurgical setup. The peripheral nociceptive stimuli also cause a neuroendocrine stress response, affecting various systems of our body leading to increased perioperative morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…One of the problems with these studies is the diversity of criteria for the definition of postoperative chronic pain, and the time that must pass has been much debated, although the exact duration of the inflammatory process is still yet to be determined. Although PCSP is defined as pain that lasts more than two months after a surgical procedure, excluding other possible causes of pain [2], some experts suggest that this period must be at least 3-6 months after surgery [17].…”
Section: Discussionmentioning
confidence: 99%
“…[1] However, it is unclear if preoperative characteristics could be used to identify shoulder arthroscopy patients at risk for poorer postoperative outcomes. Measures that may influence postoperative outcomes include psychological factors,[2] degree of pain[3] and physical functioning,[4] overall pain sensitivity,[5] and preoperative opioid use. [6]…”
Section: Introductionmentioning
confidence: 99%